Critical Thinking Ability With Improved Problem Based Learning Approach - Endra Priawasana; Waris Waris (Madrosatuna: Journal of Islamic Elementary School, 2019)
Basically students have critical thinking skills. Students 'critical thinking skills that are still low are needed in a way so that students' critical thinking skills increase, With the Problem Based Learning learning model in the hope that students' critical thinking skills will increase. the purpose of the study was to determine the effectiveness of problem based learning in improving students' critical thinking skills. This type of research is Action Research, with the stages of planning, action, observation and reflection. This research was conducted in two cycles, with each cycle consisting of two lessons. The subjects in this study were MTs students. In Ambulu sub-district. Data collection techniques use tests and non-tests. The results showed that student learning outcomes in the first cycle got a score of 45 with very low criteria, in cycle II it increased to 92.5 with very good criteria. Students' critical thinking skills in the first cycle experienced 36% classical completeness with very low criteria, in cycle II it increased to 80% with high criteria. The results of the study prove that the application of the Problem Based Learning model is very effective in improving students' critical thinking skills.